PROBLEMATIKA KEABSAHAN PEMBUKTIAN PADA IMPLEMENTASI E-LITIGASI MENURUT PERMA NO.1 TAHUN 2019 TENTANG ADMINISTRASI PERKARA DAN PERSIDANGAN DI PENGADILAN SECARA ELEKTRONIK - Bearly Deo Syahputra; Enggal Prabawuri Khotimah (UNIB Press, 2021)
The dispute resolution process in court is not always the conventional way that the parties come directly to the court, but can be done online. This was marked by the launch of the e-court on July 13 2018. With the launch of the e-court, the Supreme Court for electronics will fundamentally change the practice of court litigation. Since the issuance of the Supreme Court Regulation Number 1 of 2019 concerning administrative cases and circuit court hearings on August 19 2019, the Supreme Court Regulation Number 3 2018, the case of the Board of Directors has been declared null and void. PERMA No.1 2019 completes PERMA 3 year No. 2018 so that not only the event record can be done online or known as the name of the e-court test but also can be done electronically, for example e-ligitation. For this reason, the author tries to elaborate on the validity of the evidence in e-litigation.